2019
DOI: 10.1590/1809-4430-eng.agric.v39n4p533-536/2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tensile Strength Parallel to Grain of Wood Species

Abstract: According to the ABNT NBR 7190: 1997 standard, tensile strength of wood samples shall be defined as the ratio between the ultimate strength from a stress test and the specimen cross-sectional area (350 mm 2). However, due to the complex wood anatomy and experimental difficulties, the fractured surface in tested samples are not perpendicular to the loading direction; therefore, such fractured surface becomes larger than the sample cross section, overestimating tensile strength by this method. Using an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, due to the anisotropic characteristics of wood and the different strength of late wood and early wood layers, the fracturing mechanism does not occur in one direction [ 4 ]. Therefore, the rupture of the pine wood samples occurred at an angle of approximately 30 degrees to the direction of the fiber, as shown in Figure 10 d. Because the failure plane is not perpendicular to the applied load direction, the tensile strength consists of the total or effective stress, which has normal and shear stresses as components, as claimed by Christoforo et al [ 4 ] who studied the same phenomenon, but on tropical wood species. Analyzing the fracture of the pine wood samples subjected to tensile - compression uniaxial parallel to the fibers, it was found that the direction of normal stresses does not coincide with the main elastic directions, in addition to normal strains appear shearing strains, as shown by the generalized law of Hooke.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the anisotropic characteristics of wood and the different strength of late wood and early wood layers, the fracturing mechanism does not occur in one direction [ 4 ]. Therefore, the rupture of the pine wood samples occurred at an angle of approximately 30 degrees to the direction of the fiber, as shown in Figure 10 d. Because the failure plane is not perpendicular to the applied load direction, the tensile strength consists of the total or effective stress, which has normal and shear stresses as components, as claimed by Christoforo et al [ 4 ] who studied the same phenomenon, but on tropical wood species. Analyzing the fracture of the pine wood samples subjected to tensile - compression uniaxial parallel to the fibers, it was found that the direction of normal stresses does not coincide with the main elastic directions, in addition to normal strains appear shearing strains, as shown by the generalized law of Hooke.…”
Section: Resultsmentioning
confidence: 99%
“…Their widths, proportion and density vary, depending on the specific environment and soil conditions from year to year [ 3 ]. Wood consists of a very complex system of fibers, cells, cementing substances, etc., whose physical and chemical cohesion poses particular problems in the calculations of strength and rigidity, compared to homogeneous and isotropic materials such as, for example, metals [ 4 , 5 , 6 ]. Nowadays, wood and wood-based materials have re-entered the attention of architects and builders, being a material with numerous physical, mechanical, acoustic, and workability qualities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), and continues to extend to the plane perpendicular to the free surface of the expansion, the specimen will ultimately form a shear damage. Since the damage surface is not perpendicular to the direction of the applied load, the compressive strength consists of the total or effective stress, of which the normal and shear stresses are the components, Christoforo [6] et al conducted fracture analysis of pine specimens subjected to uniaxial compression of the tropical wood with a conforming grain and found that the direction of the positive stresses did not coincide with the main elastic direction, and that there were shear strains in addition to the positive ones, in accordance with the generalized Hooke's law. At compression parallel to the fibers, the structural change begins with an increase in the stress level, and the instability of the fibers is observed by the appearance of a number of macroscopic kinks, where the yielding of the material indicates a gradual transition of the unit cell from the initial state of an elastic material to an irreversible state.…”
Section: Mechanism Of Destructionmentioning
confidence: 99%